2017
DOI: 10.1371/journal.pone.0179218
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between microRNA-146a expression and plasma renalase levels in hemodialyzed patients

Abstract: BackgroundmicroRNA (miRNA) belongs to the non-coding RNAs family responsible for the regulation of gene expression. Renalase is a protein composed of 342 amino acids, secreted by the kidneys and possibly plays an important role in the regulation of sympathetic tone and blood pressure. The aim of the present study was to investigate plasma renalase concentration, and explore the relationship between miRNA-146a-5p expression and plasma renalase levels in hemodialyzed patients.MethodsThe study population comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…investigated the correlation between plasma renalase concentration and miR-146a-5p expression in hemodialysis patients. Patients with simultaneous low miR-146a expression and high level of renalase were found to have a significantly longer survival time compared with other patients, and both miRNA-146a and renalase levels were estimated as independent prognostic factors of hemodialyzed patients' survival time32. Micro RNA 146 has been shown to be involved in the regulation and control of inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…investigated the correlation between plasma renalase concentration and miR-146a-5p expression in hemodialysis patients. Patients with simultaneous low miR-146a expression and high level of renalase were found to have a significantly longer survival time compared with other patients, and both miRNA-146a and renalase levels were estimated as independent prognostic factors of hemodialyzed patients' survival time32. Micro RNA 146 has been shown to be involved in the regulation and control of inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-146a rs2910164 has been reported to be associated with Preeclampsia in Gestational Diabetes in the Egyptian population [68]. It is suggested that the expression of miR-146a is correlated with the levels of plasma renalase enzyme that maintains renal blood pressure [68][69][70].…”
Section: Mir-146a Rs2910164 C>gmentioning
confidence: 99%
“…Finally, renalase can hinder inflammasome activation and the release of IL-1β [ 32 , 44 , 62 ]. Taken together, renalase favors significant cytoprotection related to inflammation, oxidative stress, and apoptosis [ 28 , 29 , 30 , 31 , 32 , 37 , 38 , 39 , 50 , 59 , 62 ], whereby recent research also discloses its potential in diverse cardiac [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and kidney pathologies [ 75 , 76 , 77 , 78 ] and in the pathophysiology of COVID-19 [ 79 , 80 ]. It will be captivating to conduct future scrutiny toward an excellent comprehension of renalase pleiotropy.…”
Section: The Molecular Signature Of Renalasementioning
confidence: 99%